The many faces of Sandinista democracy - Hoyt, Katherine (Monographs in international studies. Latin America series, 1997)
Taking power in Nicaragua in 1979 as a revolutionary party, the Sandinista Liberation Front (FSLN) was willing to put its fate in the hands of the Nicaraguan people twice, in 1984 and 1990. The party wrote a democratic constitution and then, remarkably, accepted the decision of the majority by relinquishing power upon its defeat in the 1990 elections. Hoyt examines the conflicts surrounding the development of ideas within the FSLN as well as the strengths and weaknesses of its rare combination of democratic and vanguard principles. The Many Faces of Sandinista Democracy explores conflicts involving different visions of economic democracy, as well as new radical thought on participatory democracy. Hoyt brings to an international audience for the first time a study of the ideas of several Nicaraguan thinkers. A postscript deals with the aftermath of the 1996 elections, in which the Sandinistas failed to return to power.